2021
DOI: 10.1002/fsn3.2417
|View full text |Cite
|
Sign up to set email alerts
|

Study of starch aging characteristics based on Terahertz technology

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The degree of crystallinity for 6-month stored roasted seeds was 30%, which was signi cantly higher than that of freshly roasted seeds even when the moisture content of the seeds did not change. Wang et al (2021) also reported an increase in the degree of crystallinity of heatdegraded starch after aging. Rupollo et al (2011) reported increase in the degree of crystallinity of starches isolated from beans after storage at normal environmental conditions.…”
Section: Xrd Analysismentioning
confidence: 87%
“…The degree of crystallinity for 6-month stored roasted seeds was 30%, which was signi cantly higher than that of freshly roasted seeds even when the moisture content of the seeds did not change. Wang et al (2021) also reported an increase in the degree of crystallinity of heatdegraded starch after aging. Rupollo et al (2011) reported increase in the degree of crystallinity of starches isolated from beans after storage at normal environmental conditions.…”
Section: Xrd Analysismentioning
confidence: 87%
“…This proof is particularly useful in determining the crystallinity of starch, as the THz peak at 9.0 THz was correlated with the crystallinity obtained by X-ray diffraction. The THz experimental method has also been applied to real-time monitoring of the starch ageing process [158], which means that THz technology can provide an effective tool in starch-related production and processing industries, including the bioeconomy.…”
Section: Starch-based Biopolymersmentioning
confidence: 99%
“…The absorption coefficients of starch, and other plant compound have been determined [63][64][65][66][67]. Moreover, the separation of seeds based on their bacterial blight resistance or genetic modifications has been described [68,69].…”
Section: Effects On Plant and Fungi Matter 41 Plantsmentioning
confidence: 99%